2010
DOI: 10.1177/1078087410378844
|View full text |Cite
|
Sign up to set email alerts
|

Grappling with Governance: The Emergence of Business Improvement Districts in a National Capital

Abstract: Business improvement districts (BIDs) constitute a relatively new mode of urban governance in which business and property owners pay surtaxes for collectivized, privatized maintenance and development services in their respective neighborhoods. Although they are typically considered an innovative means of improving urban areas-or at the very least a benign intervention of business owners to draw new consumers-the case of Washington, D.C., shows that BIDs are also an increasingly entrenched neoliberal institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…7, No. 6;2014 While not all DDAs have a significant income stream from the incremental growth in the tax base, most Authorities can count on steadily increasing revenues. Even when the DDA's primary function is financing capital improvements with revenue bonds, continued growth of the tax base will generate increasing annual revenues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7, No. 6;2014 While not all DDAs have a significant income stream from the incremental growth in the tax base, most Authorities can count on steadily increasing revenues. Even when the DDA's primary function is financing capital improvements with revenue bonds, continued growth of the tax base will generate increasing annual revenues.…”
Section: Discussionmentioning
confidence: 99%
“…7, No. 6;2014 services provided by the BIAs appear to be complementary to, rather than competitive with, city services and solve the free-rider problems experienced by more generalized business organizations such as Chambers of Commerce (Billings & Leland, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of collaboration in BID-government relationships might not be surprising, because quite often the two parties share the common purpose of economic revitalization. However, the few studies that have analyzed BID-government relationships usually neglect the public side and focus on the private dimension of the partnership (S. Grossman, 2008 paradigms that examine all for-profit and nonprofit organizations involved in public policy making and service delivery to offer a better understanding of the type of relationships and power differentials among BIDs, between government and BIDs, and the centrality of BIDs in relation to other actors (Lewis, 2010;Morçöl & Patrick, 2006;Morçöl, Vasavada & Kim, 2014;Morçöl & Wolf, 2010;Morçöl & Zimmermann, 2006). Morçöl et al (2014) found in their longitudinal case study in downtown Philadelphia that the director of the BID, the city council, and mayors were the most central actors in the governance network, with the BID director being more central than other legally sanctioned actors.…”
Section: City Levelmentioning
confidence: 99%